Pemberdayaan Kelompok PKK Desa Klungkung Melalui Pemanfaatan Limbah Kulit Kopi Menjadi Teh Celup Cascara - Aisyah Yuristianti Utami; Devika Firta Triana; Alandi Mursalin; Ihza Alfarizhi Yudha Pratama; Aprilian Firmansyah; Danu Indra Wardhana (Journal of Community Development, 2022)
Klungkung Village becomes one of the largest coffee-producing place in Jember Regency. The waste produced from coffee processing in Klungkung Village is only sub-optimally used as additional material for fertilizer and animal feed, while the rest is thrown away. The target of this Student Creativity Program of Community Service (PKM-PM) is the Family Welfare Empowerment (PKK) group in Klungkung Village. The PKK group lack of knowledge regarding processing coffee husk waste into a various products with added value, has acted as one factor for the underdeveloping community business potential in the agricultural sector, especially in the development of new superior products. Therefore, this PKM-PM aimed to mobilize the PKK group in solving the problem of handling coffee husk waste to be used as Cascara tea in order to improve the economy and environmental quality. The method implemented in this program consisted of the preparation stage, implementation stage, science and technology assistance, monitoring and evaluation, as well as program sustainability plan. The results revealed that out of 10 target indicators, the program achievement reached 97.5%. The sustainability potential of this program has been supported by changes in the organizational structure of the PKK group into Cascara tea Small and Medium Enterprises (SMEs) which is included in the BUMDes work program. It is expected that the collaboration between the PKK group and Cascara tea SMEs will be established to support the sustainability of local economy, environment, and society aspects.